Brentano’s theory of consciousness revisited. Reply to my critics - Fisette, Denis (Argumentos - Revista de Filosofia, 2015)
I am grateful to the respondents for the time and effort they have put into their comments on my paper on Brentano’s theory of consciousness. Since many comments overlap, I will group them by theme and respond to the objections by clarifying certain aspects of my paper and by providing new elements in support of my reading of Brentano. First, I will justify the topic of my study in light of the various theories of mind that one can identify with the philosophy of Brentano. Second, I will summarize the main aspects of Rosenthal’s HOT theory, which constitutes the background of my study. I will then discuss what since Chisholm has been called “Brentano’s thesis,” which many commentators defend in light of the two theses that I attribute to Brentano early in the target paper. In the fourth section, I will discuss several objections raised against my reconstruction of Brentano and his principle of the unity of consciousness. The main hypothesis that I developed in the last sections of the target article is that the later Brentano’s introduction of the concept of mental agent aims at solving two main problems left pending in his 1874 Psychology. The first relates to the substrate of the modes of consciousness and of the complex mental state internally perceived. The second issue pertains to the status of the concomitant consciousness and to the second general thesis on consciousness: that all mental states are conscious. My hypothesis is that, to clarify the status of the Mitbewußtsein and to adequately answer the question: ”What is it for a mental state to be conscious?,” the later Brentano uses the concept of mental agent and conceives of consciousness as implicit and intransitive self-awareness.